A field study on the aerodynamics of freight trains. Issue 209 (February 2021) - Quazi, Ariq; Crouch, Timothy; Bell, James; McGreevy, Tony; Thompson, Mark C.; Burton, David
Abstract: A novel full-scale field test was undertaken to assess the aerodynamic performance of shipping containers loaded on inter-modal freight trains. The aerodynamic performance of an instrumented 48 ​ft container, located 185 ​m downstream of the locomotive, is assessed in the context of surface pressure, weather station, and GPS data sets. Previous studies on the aerodynamics of trains have been largely limited to low-resolution, reduced-order and scaled; field, numerical and wind-tunnel studies; respectively. The objective here was to determine the capacity of this novel field-based method to assess the aerodynamic performance of full-scale train containers for a large range of operating conditions. For low wind conditions, where the yaw angle is predicted to be low, measured surface pressure distributions on the front and base of the container are similar to that of past work however the magnitude of the drag coefficient was much lower, by up to 65%. This suggests that previous studies are yet to fully detail the drag profile of containers located at large downstream distance. Observed asymmetry of the pressure distribution on the front of the container are generally consistent with wind conditions measured at nearby weather stations and can be used as a proxy to determine the wind yaw angle at the train. Highlights: A novel full-scale field test was undertaken on a freight train by instrumenting a shipping container. This was done in the context of weather station, GPS, measurement uncertainty and pressure data. The pressure distribution on the front and base was similar to past work however the magnitude of the drag coefficient was lower. Pressure distribution asymmetry on the front of the container was consistent with wind conditions seen at weather stations. The asymmetry can be used as a proxy to determine the wind yaw angle.